Photometrical analysis of mirrored light pipe: From state-of-the-art on experimental results (1990–2019) to the proposition of new experimental observations in high solar potential climates. (15th November 2019) - Malet-Damour, Bruno; Bigot, Dimitri; Guichard, Stéphane; Boyer, Harry
Graphical abstract: Highlights: State of the art on experimental and numerical results on Mirrored Light-Pipe (MLP) New experimental observations on MLP in high solar potential climates. Various scenarios studied (impact of the reflection coefficient of the area to be illuminated, presence of an anticyclonic dome, type of sky or the ideal position of a sub-dome deflector). Abstract: This paper focuses on the part of Tubular Daylight Guide Systems (TDGS): the Mirrored Light-Pipe (MLP). MLP is part of the multiple specular reflection conveyors. They allow daylight to be transported and distributed in dark rooms far from traditional openings while limiting heat transmission. It involves collecting, concentrating, and diffusing sunlight using a dome placed on the roof. It is then conveyed through a highly reflective tube and diffused into a building's room using a diffuser. Previous work (Malet-Damour et al., 2017, 2016) has shown that it was necessary to identify and study the climate in which the light pipe will be installed. A state-of-the-art of experimental and numerical results was conducted over the period from1990 to 2019. It revealed that the behavior of the light pipe depends strongly on the indoor (area to be illuminated) and outdoor (meteorology) environment. This paper presents the experimental observations of studies conducted from 2013 to 2015 on Mirrored Light-Pipe in Reunion Island. The climate in which the experiment was undertaken is presented with a focus on illuminance. In 2019, this study is the only one analyzing the performance of the light pipe in extreme situations of extreme sunlight conditions (maximum global illuminance of around 200 Klux). Experimental results based on various scenarios quantified the impact of the reflection coefficient of the area to be illuminated, the presence of an anticyclonic dome, the type of sky or the ideal position of a sub-dome deflector. The results are very encouraging.